2013
DOI: 10.1152/ajpheart.00495.2012
|View full text |Cite
|
Sign up to set email alerts
|

HNO/cGMP-dependent antihypertrophic actions of isopropylamine-NONOate in neonatal rat cardiomyocytes: potential therapeutic advantages of HNO over NO˙

Abstract: RH. HNO/cGMP-dependent antihypertrophic actions of isopropylamine-NONOate in neonatal rat cardiomyocytes: potential therapeutic advantages of HNO over NO˙. Am J Physiol Heart Circ Physiol 305: H365-H377, 2013. First published May 31, 2013 doi:10.1152/ajpheart.00495.2012 is a redox congener of NO˙. We now directly compare the antihypertrophic efficacy of HNO and NO˙donors in neonatal rat cardiomyocytes and compare their contributing mechanisms of actions in this setting. Isopropylamine-NONOate (IPA-NO) elicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…22,23,28 We have previously shown that Angeli salt and IPA-NO suppress cardiomyocyte ROS production in response to hypertrophic stimuli in cultured cardiomyocytes. 18,19 In the current study, the ability of diabetes mellitus to stimulate NADPHdriven LV superoxide generation (on lucigenin-enhanced chemiluminescence, confirmed on PEG-SOD-sensitive dihydroethidium fluorescence) was absent in 1-NCAtreated mice. This trend was reproduced on LV mitochondrial uncoupling protein 3 expression.…”
Section: -Nca Treatment Protects Against Diabetes Mellitus-induced Cmentioning
confidence: 47%
See 4 more Smart Citations
“…22,23,28 We have previously shown that Angeli salt and IPA-NO suppress cardiomyocyte ROS production in response to hypertrophic stimuli in cultured cardiomyocytes. 18,19 In the current study, the ability of diabetes mellitus to stimulate NADPHdriven LV superoxide generation (on lucigenin-enhanced chemiluminescence, confirmed on PEG-SOD-sensitive dihydroethidium fluorescence) was absent in 1-NCAtreated mice. This trend was reproduced on LV mitochondrial uncoupling protein 3 expression.…”
Section: -Nca Treatment Protects Against Diabetes Mellitus-induced Cmentioning
confidence: 47%
“…In the current study, all markers of diabetes mellitus-induced cardiomyocyte hypertrophy were attenuated by 1-NCA, consistent with previous short-term findings with classical HNO donors in isolated cardiomyocytes. 18,19 To our knowledge, this is the first evidence to demonstrate antihypertrophic actions of HNO in a chronic setting in vivo. The clear, diabetes mellitus-induced cardiomyocyte hypertrophy was accompanied by a trend for increased profibrotic connective tissue growth factor expression, which was absent in 1-NCA-treated diabetic mice.…”
Section: -Nca Treatment Protects Against Diabetes Mellitus-induced Cmentioning
confidence: 65%
See 3 more Smart Citations